Serapan Kata dari Bahasa Jerman ke dalam Bahasa Indonesia : Sejarah dan Perkembangannya - Prisnandia Estepania Br Sembiring; Rachel Indah Yemima Purba; Mika Risty Silaban; Ranita Br Galingging; Nurul Azizah (Lembaga Pengembangan Kinerja Dosen, 2025)
The Indonesian language has absorbed numerous loanwords from various foreign languages, including German. Although the influence of German is not as significant as that of Dutch, Arabic, or Sanskrit, it plays a crucial role, particularly in scientific, technological, medical, and philosophical terminology. This study aims to examine the historical background, development, and adaptation of German loanwords in Indonesian. Using a qualitative approach, data collection was conducted through literature review and linguistic analysis. The findings indicate that many German words entered Indonesian through scientific and academic fields, with some undergoing phonetic and morphological adaptation. The influence of German in Indonesia continues, particularly in academic and industrial sectors, suggesting potential future linguistic integration.